Maternal and perinatal morbidity and mortality in high-risk pregnancy: a prospective study - Bablad, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: A high-risk pregnancy (HRP) is defined as one complicated by factors that negatively impact maternal and/or perinatal outcomes. These pregnancies have an increased likelihood of morbidity and mortality for both the mother and the fetus. Such cases require intensive antenatal care, sophisticated maternal and fetal monitoring, and often complex management decisions to optimize outcomes. Therefore, this study was conducted to evaluate maternal and perinatal outcomes in high-risk pregnancies. Objectives of the study were to evaluate maternal and perinatal outcomes in high-risk pregnancies, identify key factors contributing to these high-risk conditions. Methods: This prospective study was conducted from July 2023-June 2024. The study included 94 pregnant women with high risk factors with gestational age more than 28 weeks attending OPD, IPD and labor room. Results: The study included 94 pregnant women with high risk factors with gestational age ≥28 weeks. Majority of the participants were aged 20-24 years (42/44.68%). Most participants were Hindu (77/81.91%) and from lower socioeconomic classes (44/46.81%). Postpartum haemorrhage (PPH) was observed in (30/31.91%) of cases was the most common immediate complication. Surgical site infection (24/25.52%) was being other common maternal morbidities. The most common cause of perinatal morbidity was respiratory distress syndrome (13/13.83%). The perinatal mortality rate was (25/26.59%). Previous caesarean section (CS), anemia, Rh negative pregnancy was the common risk factors associated with more adverse pregnancy outcomes. Previous CS and multiple pregnancy were most commonly associated risk factors with increased risk of PPH. With vigilant and careful detection of high-risk pregnancies and timely intervention, there was no maternal mortality in our study. Conclusions: In our study we emphasise on the importance of awareness of first trimester registration, early identification of risk factors, frequent hospital visits for regular antenatal check-up, and providing quality antenatal care.